Young Shoots of White and Red Headed Cabbages Like Novel Sources of Glucosinolates as Well as Antioxidative Substances - Joanna Kapusta-Duch; Barbara Kusznierewicz (MDPI AG, 2021)
Most literature data indicate that the diet rich in plant products reduces the risk of developing chronic non-communicable diseases and cancer. Brassica vegetables are almost exclusively synthesizing glucosinolates. Glucosinolates are higher in sprouts than in mature plants, being related to the activity of the specific myrosinase involved in the degradation of glucosinolates during developmental stages. This study compares the content of total glucosinolates with their profile and, rare in the literature, also with products of their degradation. Average amounts of total glucosinolates in young shoots of white and red headed cabbage were 26.23 µmol/g d.m. and 27.93 µmol/g d.m., respectively. In addition, antioxidative properties of 21-day-old shoots of white and red headed cabbage were assessed. The area of negative peaks after post-column derivatization with the ABTS reagent, indicating antioxidant activity of young red cabbage shoots, was 20185, compared to the value determined for young white cabbage shoots (3929). The results clearly indicate that, regardless of the vegetable species, young shoots of white and red headed cabbage can be an important source of bioactive substances in the diet, thus being an important element of cancer chemoprevention.